Alkali lignin and sodium lignosulfonate additives promote the formation of humic substances during paper mill sludge composting. Issue 6 (January 2021) - Wang, Weiwu; Hou, Yi; Huang, Wenfeng; Liu, Xiaoming; Wen, Ping; Wang, Yueqiang; Yu, Zhen; Zhou, Shungui
Graphical abstract: Highlights: Adding AL and SLS increased the HS content and degree of humification. The faster evolution of quinone-like substances was the key to improve HS content. This work provided a case for comprehensive utilization of papermaking wastes. Abstract: Alkali lignin (AL) and sodium lignosulfonate (SLS) are by-products of the papermaking industry and could influence composting processes due to their rich aromatic structures. In this study, the roles of AL and SLS additives in the formation of humic substances (HS) during paper mill sludge composting were investigated. Results showed that HS content and degree of polymerization of the final products in AL (44.42 mg·g −1 and 0.70, respectively) and SLS (45.87 mg·g −1 and 1.14, respectively) treatments were appreciably higher than those of the control sample (34.36 mg·g −1 and 0.67). Excitation-emission matrix-parallel factor coupled with two-dimensional FT-IR correlation spectroscopy analysis suggested that AL and SLS additives could speed the transformation of quinone-like substances by increasing the amounts of low molecular weight lignin depolymerized products, which led to higher HS concentrations. This work provided a way of promoting HS formation and the comprehensive utilization of papermaking wastes.